The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/dcr.0000000000001047
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes After Rectal Resection for Deep Infiltrating Pelvic Endometriosis: Long-term Results

Abstract: Laparoscopic segmental rectal resection for the treatment of deep infiltrating endometriosis including the rectal wall is associated with good results in endometriotic-related symptoms, although patients should be informed about possible postoperative impairments in evacuation and incontinence. However, its clinical impact does not outweigh the benefit that can be achieved through this approach. See Video Abstract at http://links.lww.com/DCR/A547.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
5
10
0
6
Order By: Relevance
“…One possible explanation to justify a longer stay in the public hospital was the high percentage of patients (more than 30%) where the surgery was converted to an open procedure. In our cohort of private patients, the conversion rate to laparotomy was 2%, which is very similar to other series 20 .…”
Section: ■ Discussionsupporting
confidence: 91%
“…One possible explanation to justify a longer stay in the public hospital was the high percentage of patients (more than 30%) where the surgery was converted to an open procedure. In our cohort of private patients, the conversion rate to laparotomy was 2%, which is very similar to other series 20 .…”
Section: ■ Discussionsupporting
confidence: 91%
“…This distinguishes endometriosis from colorectal cancer that initially manifests with rectal bleeding. An important feature of rectal bleeding in endometriosis, along with their cyclic character, is its low intensity in the form of blood streaks in the stool, according to our study and the data reported by S. Erdem et al [10]. It must be remembered that the presence of blood or mucus in the feces requires, first of all, ruling out colorectal cancer.…”
Section: оRiginal Articlessupporting
confidence: 83%
“…En un estudio retrospectivo valoraron los resultados de incontinencia y dificultad en la evacuación posterior a la resección rectal por laparoscopia como parte del manejo de endometriosis profunda que comprometía la pared rectal, se hizo hasta 6 meses, de las 66 pacientes que se sometieron al procedimiento a 94% se les realizó laparoscopia, de las cuales 4% se convirtieron a laparotomía; 2% fueron por cirugía abierta, y además el 82% se les realizó anastomosis termino terminal, 2 pacientes presentaron insuficiencia de la anastomosis y encontraron que la dismenorrea y la dispareunia mejoraron sustancialmente en los síntomas de evacuación (p=0.002) e incontinencia (p=0.003) 31 .…”
Section: Tratamiento Quirúrgicounclassified
“…Manejo de la endometriosis rectovaginal. López Giraldo JF, et al 2019; 14 (1):[31][32][33][34][35][36][37][38] …”
unclassified